The Conflict of The Nobleman and The Peasant" In Azizi Malay Rash's Novel "Land, Oppression, Land and The Problem of Existence: A Reading That Follows Lucian Goldman's Principle of Universality - Barzan Ali Pirot; Hazhar Ahmad Abdulghafur (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
This paper is entitled "The Conflict of the Nobleman and the Peasant" and focuses on Azizi Malay Rash's novel "Land, Oppression, Land and the Problem of Existence," using Lucien Goldman's universality principle in novel sociology as its basis. Its objective is to examine the relationship and conflict between the nobleman and the peasant classes, to provide insight into the sociological characteristics of Kurdish society, and to create an opening to the sociology of Kurdish novels. The central hypothesis of this study is that the struggle between the nobleman and the peasant classes, as the landowner and the worker respectively, is deeply embedded in these two novels and is an extension of the conflict between these two classes in Kurdistan's agricultural areas. Descriptive analysis is the method used in this study, beginning with a discussion of Goldman's sociological perspectives and his views on the sociology of the novel. The paper also explores the universality principle in both novels as a sociological issue and examines its associated problems. Then, the paper analyzes the conflict between the nobleman and the peasant classes in the two novels, guided by Goldman's ideas. Finally, the paper presents its conclusions, highlighting the significant conflict between the nobility and the peasantry as two common social mentalities.